2011
DOI: 10.1074/jbc.m111.234526
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Transcriptomic Profiling of Branching in a Glycosphingolipid Biosynthetic Pathway

Abstract: Cellular biosynthesis of macromolecules often involves highly branched enzyme pathways, thus cellular regulation of such pathways could be rather difficult. To understand the regulatory mechanism, a systematic approach could be useful. We genetically analyzed a branched biosynthetic pathway for glycosphingolipid (GSL) GM1 using correlation index-based responsible enzyme gene screening (CIRES), a novel quantitative phenotype-genotype correlation analysis. CIRES utilizes transcriptomic profiles obtained from mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 55 publications
(52 reference statements)
1
22
0
Order By: Relevance
“…This value was called the p sychosine-mediated p loidy i ndex n umber (PPIN). When the six–cell line profile of PPIN was expressed as a web graph ( Figure 1C ), a similarity was found in the pattern with that of cell surface GM1 expression level, measured with the cholera toxin B subunit (CTxB), as in a previous study with the same set of cell lines ( Takematsu et al. , 2011 ).…”
Section: Resultssupporting
confidence: 66%
“…This value was called the p sychosine-mediated p loidy i ndex n umber (PPIN). When the six–cell line profile of PPIN was expressed as a web graph ( Figure 1C ), a similarity was found in the pattern with that of cell surface GM1 expression level, measured with the cholera toxin B subunit (CTxB), as in a previous study with the same set of cell lines ( Takematsu et al. , 2011 ).…”
Section: Resultssupporting
confidence: 66%
“…Globo-GSLs are also sensitive to mutations and agents affecting Golgi function. Mutations in FAPP2 or treatment of cells with brefeldin leads to a loss of globo-GSL, with increased GM3 and LacCer levels (355,356). Glycosyltransferases necessary for the synthesis of early precursors (GlcCer, LacCer, and GM3) reside in the endoplasmic reticulum and cis-Golgi network, whereas glycosyltransferases necessary for globo-GSL synthesis reside in the trans-Golgi network (357).…”
Section: Biochemistry and Synthesismentioning
confidence: 99%
“…Glycosyltransferases necessary for the synthesis of early precursors (GlcCer, LacCer, and GM3) reside in the endoplasmic reticulum and cis-Golgi network, whereas glycosyltransferases necessary for globo-GSL synthesis reside in the trans-Golgi network (357). There is evidence that ␣4GalT1 and LacCer synthase form an intra-Golgi complex to efficiently synthesize globo-GSLs (356).…”
Section: Biochemistry and Synthesismentioning
confidence: 99%
“…(iii) IEM analysis demonstrated that A4GalT is enriched in the TGN . A4GalT can bind to B4GalT6 (it is unknown whether A4GalT can also bind to B4GalT5) , suggesting that A4GalT may recruit LacCer synthases to the TGN.…”
Section: Localization and Topology Of Sphingolipid Metabolic Enzymesmentioning
confidence: 99%